Modeling above ground biomass, soil carbon determination and economic value of carbon stock of selected mangrove species in Marudu Bay, Sabah, Malaysia - Mohamad Ehsan, Norhajar Eswani (2016)
The forest absorbs CO2 during photosynthesis and stores it as organic material in plant biomass and soil. In Malaysia, accurate information on aboveground and soil carbon in the mangrove forests is lacking. Hence, the objectives of this study were to create allometric model for four selected species namely, Rhizophora apiculata, Bruguiera parviflora, Avicennia alba and Nypa fruticans and to estimate the total carbon stock for selected species including the soil carbon. In addition, economic value of each species was estimated using current carbon price. This study was conducted at Marudu Bay mangrove forest, Sabah. Forest inventory, destructive sampling and laboratory analysis for carbon content were conducted to develop the allometric models. The allometric models derived from this study for four selected species were TAGB Rhizophora apiculata=45.87+0.02×d^2 h ln(TAGB Bruguiera arviflora)=ln(0.812)+0.44×ln(d^2h))ln(TAGB Avicennia alba)=0.23+1.02×ln(dbh)TAGB Nypa fruticans=0.25+(-2.807e^(-5)×D^2 L)The results show that the average total aboveground biomass, soil carbon, carbon stock and CO2 is equivalent for Marudu Bay mangrove ecosystem are namely, 138.18 ton/ha, 225.87 tC/ha, 290.44 tC/ha and 1065.92 ton CO2e/ha. The carbon storage at Marudu bay is estimated at RM29,999.03/ha for the total mangrove ecosystem based on the REDD+ market price ($5). The study also estimates the economic value of carbon stock in Marudu bay mangroves in relation to different species. The allometric equation developed from this study can be used to assess aboveground biomass in the mangrove forest especially ii study without destructive sampling. In summary, modeling aboveground biomass, soil carbon determination and economic value of carbon stock assessment is necessary and that it will provides a protocol and valuable baseline data for monitoring biomass, carbon stock, soil carbon and economic value in the Marudu bay mangrove forest.